2002
DOI: 10.1046/j.1525-1438.2002.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative selection of patients with low-stage endometrial cancer at high risk of pelvic lymph node metastases

Abstract: Abstract. van

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
9
0
4
Order By: Relevance
“…We examined the full text of the remaining 50 articles. Finally, 26 studies were discarded because they did not meet inclusion criteria and the remaining 24 studies were included in the review and meta‐analysis. No additional relevant studies were found from references cited in the papers included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the full text of the remaining 50 articles. Finally, 26 studies were discarded because they did not meet inclusion criteria and the remaining 24 studies were included in the review and meta‐analysis. No additional relevant studies were found from references cited in the papers included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Bei Frauen unter 60 Jahren erschweren Myome bzw. Adenomyosis uteri die Abschätzung der myometranen Invasionstiefe[84]. Eine Überschätzungs-gefahr besteht zudem bei einem kleinen Uterus, einem atrophen Myometrium, exophytischem, polypösen Tumorwachstum oder Pyometra[84].Aktuell ist die Standardmethode im präoperativen Management das MRT.…”
unclassified
“…Adenomyosis uteri die Abschätzung der myometranen Invasionstiefe[84]. Eine Überschätzungs-gefahr besteht zudem bei einem kleinen Uterus, einem atrophen Myometrium, exophytischem, polypösen Tumorwachstum oder Pyometra[84].Aktuell ist die Standardmethode im präoperativen Management das MRT. Im Vergleich zur Sonographie und zum CT stellt das MRT, vor allem mit Kontrastmittelanwendung, die derzeit beste Möglichkeit zur Evaluation der myometranen und zervikalen Invasion dar[5,32,54,64,67,90].…”
unclassified
“…Ses performances dans le bilan d'extension du cancer de l'endomètre sont très diversement appréciées, et sa sensibilité varie de 37 à 100 % selon les études [3,5,9,[11][12][13][14][15][16][17][18][19][20] (Tableau 5).…”
Section: Discussionunclassified